From Body Narratives to Cultural Identity: A Study of Ritualised Representations in Modern Sound Media - Junru Zhang (Studies in Social Science & Humanities, 2024)
For modern people who have been under the hegemony of visual picture for a long time, the sensory balance in the Internet era is the key to releasing body appeals and getting rid of individual heterogeneity. The unique sense of imagination, immersion and companionship created by modern sound media to the audience can directly arouse emotional resonance, so as to achieve the group identity of sound field culture. Based on the perspective of ritual view of media, this paper analyzes the ritualized representation mode of modern sound media from two dimensions: the morphological evolution of body narrative of sound media and the deep aggregation of auditory culture, and thus corresponds to the dual aspects of ritualized representation: the embodied presentation and landscape modeling of sound media. By clarifying the subject’s holistic and differentiated identity cognitive thinking in media practice and the social auditory cultural aggregation phenomenon, the ritualized signs of modern sound media are deeply investigated in order to provide a theoretical perspective for the cultural research of modern sound media.